Brain blood flow during morning and afternoon rowing performance - Faull, O. K.; Cotter, J. D.; Lucas, S. J. E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Regulating brain blood flow acutely and chronically has important implications for exercise performance. Despite evidence of circadian rhythms in cerebral blood flow (CBF), blood pressure (BP), cerebrovascular responsiveness to carbon dioxide (CO2) and cerebrovascular autoregulation, all of which peak in the afternoon, the combined influence of these underlying circadian rhythms for exercise performance is yet to be explored, despite performances in several sports being reported to peak in the early evening. We aimed to compare the CBF responses to rowing exercise at different times of day, since rowing has large haemodynamic effects and it is performed at opposing ends of a day. We hypothesised that a higher CBF and improved regulation in the afternoon would be positively related to maximal rowing performance. Methods: Twelve trained male rowers completed an incremental rowing exercise protocol and a 2000-m maximal rowing ergometer test in the morning (7 am) and afternoon (4 pm), one week apart. Middle cerebral artery velocity blood flow (MCAv) and cerebral (prefrontal) and muscular (vastus lateralis) tissue oxygenation were recorded continuously using Transcranial Doppler sonography and Near Infrared Spectroscopy (NIRS), respectively. Heart rate and partial pressure of end-tidal carbon dioxide (PETCO2) were also measured throughout. Results: Maximal rowing ergometer time trial performance was faster (3.4 s; 95% CI 0.9-5.8 s) in the afternoon; however MCAv remained consistent between the two trials during maximal exercise (~1 cm/s difference; p = 0.60). Resting MCAv and BP also showed no time of day differences (~1 cm/s and 1.1 mm Hg differences; p > 0.05), and neither did prefrontal haemodynamics during time trials. MCAv increased from rest (68 ± 12 cm/s (SD)) during all intensities of exercise (80±11; 81±12; 80±11; 84±13 cm/s for 50%, 75%, 2000-m max and 30 s max, respectively), despite significant decreases in PETCO2 (42±2; 40±2; 34±2, 36±3 mm Hg, respectively) from rest (40 mm Hg). Prefrontal oxygenated haemoglobin decreased consistently across 2000 m at both times of day (morning: 208 ± 117 ìM•cm in the morning; afternoon 276 ± 177 ìM•cm; p = 0.11), whereas in the muscle it dropped more in the afternoon (238 ± 96 vs 137 ± 66 ìM•cm; p < 0.01). Conclusion: 2000-m rowing ergometer performance was better in the afternoon, but this was not in conjunction with any differences in MCAv or cerebral oxygenation at rest or during maximal exercise. We suggest that changes in peripheral metabolism and contraction velocities, due to possible circadian increases in muscle temperature, contributed to the better afternoon performance. In addition, rowing performance did not produce the inverted-U profile of brain blood flow with exercise intensity that is observed in other sports.